空间机械臂关节非线性摩擦建模及补偿 - 付建宁; 詹涵菁; 黄文康 (Jixie chuandong)
Aiming at the non-linear friction problem of spatial robotic arm joints,non-linear friction modeling and compensation methods are proposed.Firstly,the relationships between the non-linear friction and the motor current and the non-linear friction and the angular acceleration are derived based on the established dynamics equations of robotic arm joints.Then,the angular acceleration is estimated based on the Kalman-Newton prediction machine which is designed through the sampled angle signal.Through the angular acceleration and sampling current,the friction torque is calculated,and an exponential friction model is established.Finally,based on the friction model,a feed-forward compensation controller is designed to compensate the non-linear friction.The suitability of this methods is verified via a series of robotic arm joint driving experiments.